(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
Drying is an important stage in the preparation of bamboo blades for kelarai panel production because it directly affects the final moisture content of the material. In current practice, conventional sun drying remains widely used by local craftsmen due to its low cost and simple application, although the method is highly dependent on weather conditions and may produce inconsistent results. This study aims to compare the moisture content of Semantan bamboo (Gigantochloa scortechinii) blades subjected to sun drying and oven drying in order to determine the more effective drying method for kelarai production. An experimental approach was adopted in which bamboo samples were dried under different conditions, namely sun drying, oven drying at 30°C for 12 hours, and oven drying at 50°C for 2 hours, with and without boron treatment. Moisture content was calculated based on the difference between initial and final weight after drying. The findings show that oven drying produced lower and more consistent moisture content than sun drying, while oven drying at 50°C for 2 hours recorded the lowest moisture content among all methods tested. These results indicate that controlled drying provides a more reliable approach for reducing moisture content in bamboo blades intended for kelarai panel production.